Aurora Burning - Kaufman, Amie; Kristoff, Jay (Kaufman, Amie. Aurora cycle, 2020)
"Our heroes are back. Kind of. First, the bad news: an ancient evil - you know, your standard consume-all-life-in-the-galaxy deal - is about to be unleashed. The good news? Squad 312 is standing by to save the day. They've just got to take care of a few small distractions first. Like the clan of gremps who'd like to rearrange their favourite faces. And the cadre of illegit GIA agents with creepy flowers where their eyes used to be, who'll stop at nothing to get their hands on Auri. Then there's Kal's long-lost sister, who's not exactly happy to see her baby brother, and has a Syldrathi army at her back. With half the known galaxy on their tails, Squad 312 has never felt so wanted." --